Valuing the unknown: could the real options have redeemed the ailing Western Australian junior iron ore operations in 2013–2016 iron price crash - Ajak, A.; Lilford, Eric; Topal, Erkan (Taylor & Francis, 2018)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. The inability of existing analytical models to accurately predict future events has, at times, led to the economic failure of mining operations whose financial viabilities were determined based on static assumptions, leaving operational managers with little room to make future decisions. Therefore, the application of a robust decision-making tool, such as Real Options (RO) can minimise losses and more accurately express uncertainty. This paper has considered a stochastic simulation to analyse ROs for a real case iron ore mine, which closed in April 2016. In comparing the net present value from the traditional discounted cash flow (DCF) method to delay, to abandon the operations and to stage the investment options, the ROs method increased the project value by between 56% and 195% depending on the volatility. As a new contribution, a managerial flexibility domain map is proposed in this paper. Thus, flexibility in mining operations creates agility, increases value and mitigates financial losses.